(untitled) (Multidisciplinarni Pristupi u Edukaciji i Rehabilitaciji, 2019)
Introduction: Among the various symptomatic manifestations of mental insufficiency, besides the obvious speech disorders, there is the presence of functional and/or organs vocal pathologies. The aim of the research was to determine the acoustic and aerodynamic characteristics of the voice of children with mild and moderate intellectual difficulties and to examine the existence of differences in the mentioned parameters between these two groups of respondents. Methods: The study was conducted on a sample of 38 children with a diagnosis of mild and moderate intellectual difficulties, chronological ages of seven to 12 years old, attending special classes at regular schools. Results: The results showed that children with mild and moderate levels of intellectual difficulties have normal values of the laryngeal tone. However, the value of the frequency perturbation was increased in children with moderate intellectual difficulties, while the value of amplitude perturbation was increased in both groups of respondents. The measured aerodynamic parameter was at the line of pathological value in subjects with mild intellectual difficulties, and in subjects with moderate intellectual difficulties measured aerodynamic parameter was pathological. The results also show that both groups of participants differ significantly in the acoustic parameter describing the frequency perturbation and in the aerodynamic parameter of the maximum phonation time. Conclusion: Discrepancies in the mentioned voice evaluation parameters point to the need for timely diagnosis and treatment of not only speech and language but also the voice of the population of children with mild and moderate intellectual difficulties.